Application of an Expert System for Disease Identification in Rice Plants Using the Certainty Factor Method - Naufal Irwan (Journal of Intelligent Decision Support System (IDSS), 2020)
Rice disease is a biotic stress that can reduce yields and can even cause crop failure. Therefore, to get optimum yields in rice cultivation, it is necessary to control disease. Disease is controlled with an Integrated Disease Management (IPM) approach which is integrated into the PTT model. The lack of experts is also a constraint on agriculture. An expert system application is needed to replace the shortage of experts. The application of an expert system for identifying diseases in rice plants applies the Certainty Factor method in determining the identification results. Several supporting tools are also used, such as PHP as a programming language, MySQL as a database, and XAMPP as a local server. The results of functional testing on the application have been running 100% and the calculation of the level of validity of the results is in accordance with the results of the experts. In user testing, 82.67% said it was good, 14.67% said it was sufficient, and 2.67% said it was not enough. Based on these results, the application of an expert system for identifying rice plant diseases has been well received.